1997
DOI: 10.1093/arclin/12.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the cognitive behavioral driver's inventory to distinguish malingerers from brain-damaged subjects

Abstract: The Cognitive Behavioral Driver's Inventory (CBDI) was analyzed for its ability to discriminate brain-damaged patients from intact subjects who feigned brain-damage. In a sample of 251 neurologically impaired patients and 48 malingering volunteers, the computer-administered distinguished most malingerers from genuine patients. A jackknifed count revealed that the CBDI had 90% sensitivity for detecting malingerers, and 98% specificity for detecting non-malingering brain damaged patients. Success was due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The methodology described in Ray et al (1997) was implemented exactly except that the 53 new participants attended a "coaching" session prior to testing.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodology described in Ray et al (1997) was implemented exactly except that the 53 new participants attended a "coaching" session prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the profile includes response time data, which we hypothesize to be more resistant to the effects of coaching. Ray et al (1997) found the CBDI to have 90% sensitivity for detecting student laboratory malingerers (N = 45) and 98% specificity for detecting non-malingering brain-damaged patients. However, participants in this study, though motivated by financial reward to malinger brain damage, were naive with regard to how brain-damaged individuals might perform on neuropsychological tests.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations